The Role of Nursing in Seasonal Crowd Management - Almatrafi, Nouf.K.; Alsaadi, Abeer.M.; Almatrafi, Hajar.K.; Alsaeedi, Afaf.I.; Alghamdi, Jumana.S.; Albushra, Khalid.O.; Alanazi, Fatimah.A.; Alshalawi, Muidh.N.; Althobaiti, Hatem.S.; Alsofyani, Ameera.O.; Althagafi, Abdulslam.S.; Alyamany, Hanya.A.; et al. (Journal of Posthumanism, 2024)
Every year the Ministry of Health in Saudi Arabia announces the opening of applications to those who wish to work on Hajj. A certain number of applicants are nominated, yet many nurses continue to apply to participate during Hajj ever year. Although nurses are under great work pressure during Hajj, many nurses still apply for the approval to participate in Hajj. But as a life savior, communicator, therapist and first responder in case of mass gathering and disaster, the role of nurses is inevitable. The aim of this study is to identify the motivations of nurses to work during Hajj. Furthermore, to explore the motivations that lead nurses to participate in the Hajj season and to explore the challenges faced during the Hajj season. The study used a descriptive qualitative study design. The data were analyzed using SPSS Ver. 22.0.